Monitoring the behaviour of Massingir dam in Mozambique - Marcelino, J. (2012)
Massingir, an earth fill dam with nearly 5 km long and a maximum height of 47 m is the 2nd largest dam in Mozambique. The reservoir has a maximum storage capacity of about 2,800 hm³ and the flooded area, at the Normal Water Level (NWL), is 138 km². Dam construction took place between 1971 and 1977, but because of armed conflict and funding issues, the construction was incomplete, missing the installation of the spillway gates (six gates) and the hydro-power station. During the first filling in 1977 it exhibited serious behaviour problems on the foundation, namely because piping have occurred in large extensions of the right bank dike. Its exploitation was thus, limited, and only after the rehabilitation works completed in 2006, the normal exploitation of the reservoir begun, although still without the power house. The rehabilitation included the following tasks: i) partial treatment of the foundation, by grouting, ii) construction of a stabilizing berm downstream of the dam's right dike, iii) construction of relief wells along the right bank of the dike and the main valley; iv) the lift of 1 m of the crest elevation; v) construction of a concrete parapet on the crest; vi) rehabilitation of the rip-rap; vii) the installation of the spillway gates, viii) repair of hydro-mechanical equipments of the bottom discharges, ix) rehabilitation of the monitoring system and some other minor works. As a result of the re-filling, a major accident occurred at the exit of the bottom outlet discharges, reconditioning again the exploitation of the reservoir. Currently the dam is undergoing a new intervention to increase the capacity of the spillway flood discharges and to repair the bottom outlets exit. The dam has a monitoring system installed, from which several physical quantities are obtained, on the basis of which it is possible to establish statistical models used for assessing its behaviour and to predict its response for different scenarios. Furthermore, the models allow to establish criteria for attention and alert to adopt in future exploration.